Comparative analysis of the switching energy losses in GaN HEMT and silicon MOSFET power transistors - Мрвић, Јован; Вукић, Владимир (Proceedings, Electrical engineering institute "Nikola Tesla", 2020)
The subject of this paper is the mutual comparison of switching energy losses in cascode gallium nitride HEMT and silicon "superjunction" MOSFET transistor, designed for a maximum operating voltage of 650 V. For the analysis of transistor switching characteristics, the double pulse test method was implemented, using detailed computer simulation models developed in programs of the SPICE family. Data on transient turn-on and turn-off processes were generated, using the LTspice simulation tool, in a wide range of drain currents, with two different gate resistance values of the tested transistors. The obtained results indicate superior switching characteristics of gallium nitride devices in relation to silicon components, especially during the transistor operation with high drain currents. During the one transistor switching cycle, the total energy losses in the GaN HEMT were simulated, for a drain current of 30 A, being five to eight times lower, in comparison with the examined Si MOSFET transistor.
Keywords: gallium nitride (GaN); silicon (Si); cascode transistor; HEMT; superjunction MOSFET; SPICE simulation; energy losses